2022
DOI: 10.1097/ijg.0000000000002054
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and Reproducibility of 4.5 by 4.5 mm Peripapillary Optical Coherence Tomography Angiography Scans in Glaucoma and Non-Glaucoma Eyes

Abstract: Précis: Peripapillary vessel parameters from optical coherence tomography angiography (OCTA) 4.5×4.5 mm scans in nonglaucomatous and glaucomatous eyes showed high repeatability and reproducibility, with higher reliability for commercially developed OCTA parameters compared with custom OCTA parameters. Purpose:The purpose of this study was to assess intrasession repeatability versus intersession reproducibility of peripapillary vessel parameters from 4.5×4.5 mm OCTA scans in nonglaucomatous eyes and glaucomatou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…The imaging modality used in our study, Zeiss Angio-Plex based on the OMAG system, is a spectral-domain OCTA with complex signal-based OMAG and is one of the most widely used commercially available OCT systems in actual clinical settings. Past studies have shown better repeatability and reproducibility in 4.5 × 4.5-mm sized scans of the radial peripapillary capillary plexus and macula compared to the 6 × 6-mm sized images of the previous version [4,36]. The results of the study using peripapillary images were similar even when the scans were taken from the same clinical setting using the same technology [36].…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The imaging modality used in our study, Zeiss Angio-Plex based on the OMAG system, is a spectral-domain OCTA with complex signal-based OMAG and is one of the most widely used commercially available OCT systems in actual clinical settings. Past studies have shown better repeatability and reproducibility in 4.5 × 4.5-mm sized scans of the radial peripapillary capillary plexus and macula compared to the 6 × 6-mm sized images of the previous version [4,36]. The results of the study using peripapillary images were similar even when the scans were taken from the same clinical setting using the same technology [36].…”
Section: Discussionmentioning
confidence: 66%
“…Past studies have shown better repeatability and reproducibility in 4.5 × 4.5-mm sized scans of the radial peripapillary capillary plexus and macula compared to the 6 × 6-mm sized images of the previous version [4,36]. The results of the study using peripapillary images were similar even when the scans were taken from the same clinical setting using the same technology [36]. The significance of the current study lies in the examination of the values of vascular parameters derived from the most commercially available OCTA in glaucoma clinics and the investigation of the correlation of vascular parameters with representative structural and functional parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be useful to investigate the repeatability and reproducibility of our device and software in control subjects to determine whether a difference in OCTA parameter measurements in a given patient is clinically significant or within the accepted “noise” of the technology and the patient’s daily physiological variation. Studies have shown good intra-session repeatability and good inter-session reproducibility of OCTA vessel parameter measurements in healthy and glaucomatous eyes using commercial software for OCTA devices [ 43 , 44 , 45 , 46 ]. The inter-session coefficient of repeatability is the best measure for this assessment as it represents the estimated range in which the difference between two repeated measurements for a given eye falls 95% of the time [ 43 ].…”
Section: Discussionmentioning
confidence: 99%